2014
DOI: 10.1017/s0033291714000981
|View full text |Cite
|
Sign up to set email alerts
|

Deep brain stimulation for obsessive–compulsive disorder: a systematic review and meta-analysis

Abstract: DBS may show promise for treatment-resistant OCD but there are insufficient randomized controlled data for other psychiatric conditions. DBS remains an experimental treatment in adults for severe, medically refractory conditions until further data are available.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
60
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 81 publications
(61 citation statements)
references
References 33 publications
(92 reference statements)
0
60
0
1
Order By: Relevance
“…Nangunoori et al (2013) performed a pooled analysis based on the statement that there are scarce DBS randomized clinical trials, and intended to gather a larger number of subjects reported individually or in case series [37]. Kisely et al (2014) chose to perform a meta-analysis of sham-controlled randomized clinical trials [50]. Therefore, while the first review included a larger number of studies, the second evaluated studies with a more consistent design.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Nangunoori et al (2013) performed a pooled analysis based on the statement that there are scarce DBS randomized clinical trials, and intended to gather a larger number of subjects reported individually or in case series [37]. Kisely et al (2014) chose to perform a meta-analysis of sham-controlled randomized clinical trials [50]. Therefore, while the first review included a larger number of studies, the second evaluated studies with a more consistent design.…”
Section: Resultsmentioning
confidence: 99%
“…Kisely et al (2014) performed a meta-analysis to evaluate DBS effects on major depressive disorder, anorexia and OCD [50]. Due to the inclusion and exclusion criteria for the clinical trials, they only evaluated five OCD trials [40,48,49,51,52].…”
Section: Resultsmentioning
confidence: 99%
“…Similarly, a meta-analysis that included 10 studies with 64 OCD patients reported some heterogeneity in the response, but an overall significant clinical improvement, with a 2.77 SP reduction in Y-BOCS score [10]. Another meta-analysis also shows a partial symptom remission (mean Y-BOCS reduction of 9 points), but no significant impact in comorbid anxiety or depression [11].…”
Section: Dbs In Ocdmentioning
confidence: 93%
“…DBS for epilepsy 232 DBS was found to decrease seizure frequencies in patients with 233 medically refractory epilepsy (Fisher et al, 2010;Fridley et al, 234 2012;Morrell, 2011;Sprengers et al, 2014). Based on the imaging studies, the subgenual cingulate area 261 (Brodmann area 25 or Cg25) was shown to be an important nodal 262 point in limbic-cortical circuit in depression with increased 263 metabolic rate and cerebral blood flow in depressed patients 264 (Mayberg et al, 2000;Seminowicz et al, 2004 Kisely et al, 2014). It was postulated that the 285 clinical improvement was achieved by normalizing the dysfunc-286 tional orbitofrontal circuits (Bourne et al, 2012) and by increasing 287 thalamocortical inhibition (Lozano and Lipsman, 2013).…”
Section: Essential Tremor 221mentioning
confidence: 99%